Beyond words: Academic writing identities and imaginative (artistic) selves. Issue 3 (1st December 2018) - Badenhorst, Cecile; McLeod, Heather; Toll, Haley
Exploring the de/construction of our imaginative (artistic) selves in relation to our academic writing, we foreground the notion that imaginative processes are part of the assembly of self/selves even as they are part of that de/construction. These imaginative selves are important for our professional identities and the daily negotiations we undertake in the context of institutional norms and expectations. Significant for our outward identities, these imaginative selves allow us to speak from different positions, possibly ones that resist conformity and compliance and actively contribute towards a personally ethical academic identity. Through narratives, images and a post-structural research lens, we explore our 'hidden' imaginative (artistic) selves in relation to our academic (writing) selves. Two themes emerged from the analysis of our narratives: (1) Into the unknown; and (2) Finding ourselves. We suggest that engagement with artistic, expressive and aesthetic activities in our personal time are important for processing – through metaphor and sensory means – our understanding of our professional identities, particularly, our writing selves. These incursions into our subjectivities reveal incongruity and ambiguity but also provide a sense of renaissance and regeneration.